Use of local anesthetic for the resolution of benign anorectal pathology in the Social Security Institute of Guatemala (IGSS) - Hernández,Pablo Maldonado (2020)
Abstract Introduction The use of regional anesthetic block has increased, along with the reduction of the use of spine anesthetic in this particular field of surgical activity. In the last decade ambulatory surgery and local anesthetic have lower surgical time, complications of the anesthetic itself, and hospital stay. Objective Presenting the results obteained with the use of local anesthesic and analgesic in the resolution of benign anorectal pathology. Methods A prospective, longitudinal, study, from January 2017 to December 2017, patients were classified according to surgical procedures performed using analogical visual scale to determine the pain tolerance, during the procedure, 24 h later and in the 5th post operative day. Results 253 procedures were performed with 116 local analgesia, 116 were male (45.86%) years 137 female (54%), Milligan-Morgan hemorroidectomy with Ligasure and fistulotomy were the most frequently performed procedures 32% each, followed by biopsy 16%, left lateral esfinterotomy 13% and cutaneous appendix 12%. Females presented better pain tolerance than males patients (92 vs. 81), 68% referred good tolerance through the procedure. Conclusions 68% of all the patients obtained good pain tolerance through anal anesthetic block, females manifested better pain tolerance than males, in non-complicated anorectal pathology local block ha shown to be safe and reproductible for the treatment of benign anorectal pathology in the Guatemalan Institute for Social Security.